2022
DOI: 10.3390/ijms23063104
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Autophagy by Low-Dose Silica Nanoparticles Enhances Testosterone Secretion in Leydig Cells

Abstract: Silica nanoparticles (SNPs) can cause abnormal spermatogenesis in male reproductive toxicity. However, the toxicity and toxicological mechanisms of SNPs in testosterone synthesis and secretion in Leydig cells are not well known. Therefore, this study aimed to determine the effect and molecular mechanism of low doses of SNPs in testosterone production in Leydig cells. For this, mouse primary Leydig cells (PLCs) were exposed to 100 nm Stöber nonporous spherical SNPs. We observed significant accumulation of SNPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 50 publications
(68 reference statements)
1
11
0
Order By: Relevance
“…The average diameter of SNPs was 109.0 ± 14.5 nm which was determined by randomly counting and measuring more than 500 particles ( Figure 1 B). The hydrodynamic diameter of SNPs and the zeta potential of SNPs can be obtained from our previous study [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The average diameter of SNPs was 109.0 ± 14.5 nm which was determined by randomly counting and measuring more than 500 particles ( Figure 1 B). The hydrodynamic diameter of SNPs and the zeta potential of SNPs can be obtained from our previous study [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two BECLIN-1 shRNA vectors (shBecl1-1 and shBecl1-2) and a negative control shRNA vector (shNC) were preserved in our laboratory [ 26 ]. The recombinant BECLIN-1 lentiviruses were packaged using HEK 293T cells as described previously [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that LC-3 could promote the formation of autophagosomes, and MDC level reflected the formation of autophagosomes [ 20 , 21 ]. Thus, LC-3 and MDC staining were performed to investigate the effect of HSYA on cell autophagy.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative stress induces autophagy, resulting in apoptosis [ 10 ]. Our recent studies show that SNPs (110 nm, spherical) reduce the population of Leydig cells and disorganization of spermatogenic cell layers under 25 mg/kg dose in vivo, enhance testosterone secretion under 100 μg/mL [ 11 ], and suppress Leydig cell apoptosis via the activation of caspase-8 under 400 μg/mL in vitro [ 12 ]. Autophagy dysfunction results in the accumulation of impaired organelles and unfolded/misfolded proteins, ultimately leading to cell death [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%